2007
DOI: 10.2202/1934-2659.1066
|View full text |Cite
|
Sign up to set email alerts
|

Passivity Based Dynamic Controllability Analysis for Multi-Unit Processes

Abstract: In this paper, a simple dynamic controllability analysis is developed to analyze the achievable control performance of different control structures for multi-unit processes. Based on the concept of passive systems, this approach extends the concepts of Decentralized Integral Controllability (DIC) and Block-Decentralized Integral Controllability (BDIC) so that process dynamics are considered. By using particular multipliers that represent different control structures, the frequency ranges in which perfect contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Passivity/dissipativity‐based methodology is a new development for plant‐wide operability analysis. Bao and coworkers93–100 have done a great deal of research in the field of controllability analysis based on passivity 101. In 2007, they gave a detailed introduction to this approach 102.…”
Section: Methodologies For Controllability Analysismentioning
confidence: 99%
“…Passivity/dissipativity‐based methodology is a new development for plant‐wide operability analysis. Bao and coworkers93–100 have done a great deal of research in the field of controllability analysis based on passivity 101. In 2007, they gave a detailed introduction to this approach 102.…”
Section: Methodologies For Controllability Analysismentioning
confidence: 99%
“…Passivity/dissipativity-based methodology is a new development for plantwide operability analysis. Bao and coworkers [93][94][95][96][97][98][99][100] have done a great deal of research in the field of controllability analysis based on passivity. 101 In 2007, they gave a detailed introduction to this approach.…”
Section: Controllability Analysis For Nonlinear Processesmentioning
confidence: 99%
“…Morari et al 19 RHP Zeros LD Russell and Perkins 20 Time delay NLD Skogestad and Morari 21,22 CN LD Bogle and Rashid 23 CN LD Psarris and Floudas 24,25 Time delay LD Narraway and Perkins 26 Economic back-off LD Skogestad and Hovd 27 RGA, CLDG LD Weitz and Lewin 28 Disturbance cost LD Soroush 29 Time delay LD Zafiriou E, Chiou 30 Process zeros LD Cao and Perkins 31 Output deviation NLD Lewin and Bogle 32 RGA LD Young and Swart 33 Economic back-off LD Ross and Swartz 34 Closed-loop performance LD Havre and Skogestad 35 NMP performance NLD Gal and Varga 36 Structural controllability LD Chenery and Walsh 37 Output deviation LD Zheng and Mahajanam 38 Dynamic controllability LD Kim and Yoon 39 Structural controllability NLD Byungwoo et al 40 Structural controllability NLD Kuhlman and Bogle 41 NMP performance NLD Karafyllis and Kokossis 42 Disturbance resiliency NLD Meeuse and Tousain 43 Closed-loop performance LD Maya-Yescas and Aguilar 44 RGA NLD Kuhlman and Bogle 45 NMP performance NLD Cao and Yang 46 Singular value, zeros LD Engell et al 47 RPN LD Meel and Seider 48 NMP performance NLD Santoso et al 49 Passivity NLD Srinivasan and Bonvin 50 Output controllability NLD Kaymak and Luyben 51 Dynamic controllability NLD Santoso et al 52 Passivity LD Papadopoulos and Seferlis 53 Sensitivity analysis NLD Kaistha et al 54 Closed-loop performance NLD increasing proximity of the zeros to the imaginary axis. Studies 58 have shown that RHP zeroes cannot be shifted to different locations by ou...…”
Section: Cn Ldmentioning
confidence: 99%
“…Thus, this approach can be used to study the effects of interactions on plantwide operability. In our past work, the dissipativity of a process was linked to its controllability to develop several process operability analysis tools. , However, the above framework requires the information on the dissipativity of nonlinear process units, which is often very difficult to obtain. This is perhaps the biggest hurdle in implementing such an approach by process design engineers who do not necessarily have nonlinear control expertise.…”
Section: Introductionmentioning
confidence: 99%